Periductal Mastitis, a Disease with Distinct Clinicopathological Features from Granulomatous Lobular Mastitis - Zhou F; Liu L; Wang F; Yu L; Xiang Y; Zheng C; Huang S; Yang Z; Yu Z (Dove Medical Press, 2024)
Fei Zhou,1,2 Liyuan Liu,1,2 Fei Wang,1,2 Lixiang Yu,1,2 Yujuan Xiang,1,2 Chao Zheng,1,2 Shuya Huang,1,2 Zhen Yang,1 Zhigang Yu1,2 1Department of Breast Surgery, The Second Hospital of Shandong University, Jinan, Shandong, 250033, People's Republic of China; 2Institute of Translational Medicine of Breast Disease Prevention and Treatment, Shandong University, Jinan, Shandong, 250033, People's Republic of ChinaCorrespondence: Zhigang Yu, Department of Breast Surgery, The Second Hospital of Shandong University, Jinan, Shandong, 250033, People's Republic of China, Tel +86-531-85875048, Email yzg@medmail.com.cnPurpose: Periductal mastitis (PDM) is a chronic inflammatory lesion of the breast with an unknown etiology, and it is difficult for clinicians to differentiate it from granulomatous lobular mastitis (GLM), although they have different treatment strategies and prognosis. This study aimed to investigate the differences in their clinicopathologic features to inform treatment strategies.Patients and Methods: Between 2011 and 2020, 121 patients diagnosed with PDM and 57 patients with GLM were retrospective analysis. Patient data were extracted on demographics, clinical presentation, pathologic characteristics, treatments and clinical response. Histopathological evaluations were performed on core needle biopsy specimens. Immunohistochemical stains using antibodies against CD3, CD4, CD8, CD20, and CD138 was performed to define immune cell infiltration.Results: PDM patients had a higher median age compared to GLM patients (38 vs 32, p< 0.001). PDM was primarily located in the areolar area, while GLM predominantly affected the peripheral quadrant of the breast (56.20% vs 75.44%, p< 0.001). Histopathologically, more ductal dilatation (90.08% vs 3.51%, p< 0.001), ductal wall thickening (47.93% vs 1.75%, p< 0.001), and ductal rupture (44.63% vs 5.26%, p< 0.001) were observed in PDM. GLM presented with significantly more granuloma (94.74% vs 10.74%, p< 0.001), microabscess (68.42% vs 28.93%, p< 0.001), and lipid vacuole (40.35% vs 8.26%, p< 0.001) formation than PDM. Immunohistochemical analysis revealed a significant presence of CD20+ B lymphocytes in PDM and a higher prevalence of CD8+ T lymphocytes in GLM, indicating differing immune responses. Treatment outcomes varied, with PDM patients responding well to surgery and anti-mycobacterial therapy, while GLM patients showed favorable responses to steroid therapy.Conclusion: PDM is a specific entity with a similar clinical presentation but distinct histopathological features and immune profiles to GLM. Further research is needed to elucidate the pathogenesis and optimize therapeutic approaches for these breast inflammatory conditions.Keywords: etiology, granulomatous lobular mastitis, immunology, pathology, periductal mastitis